C-reactive protein-complement factor H axis as a biomarker of activity in early and intermediate age-related macular degeneration - Giralt, Lena; Figueras-Roca, Marc; Eguileor, Beatriz De Luis; Romero, Barbara; Zarranz-Ventura, Javier; Alforja, Socorro; Santiago, Francisca; Bolaños, Jennifer; Lozano, Francisco; Dotti-Boada, Marina; Sala-Puigdollers, Anna; Dura, Paula; et al. (Frontiers in Immunology, 2024)
To determine and compare the serum levels of complement Factor H (FH), monomeric C-Reactive Protein (mCRP) and pentameric C-Reactive protein (pCRP) in patients with age-related macular degeneration (AMD) and to correlate them with clinical, structural and functional parameters.Methods: Cross-sectional observational study. One hundred thirty-nine individuals (88 patients and 51 healthy controls) from two referral centers were included and classified into three groups: early or intermediate AMD (n=33), advanced AMD (n=55), and age and sex matched healthy controls (n=51). Serum levels of FH, mCRP, and pCRP were determined and correlated with clinical and imaging parameters.Results: Patients with intermediate AMD presented FH levels significantly lower than controls (186.5 µg/mL vs 415.2 µg/mL; p=0.039) and FH levels <200 µg/mL were associated with the presence of drusen and pigmentary changes in the fundoscopy (p=0.002). While no differences were observed in pCRP and mCRP levels, and mCRP was only detected in less than 15% of the included participants, women had a significantly higher detection rate of mCRP than men (21.0% vs. 3.8%, p=0.045). In addition, the ratio mCRP/FH (log) was significantly lower in the control group compared to intermediate AMD (p=0.031). Visual acuity, macular volume, and foveal thickness were significantly lower in the advanced AMD group, and choroidal thickness was significantly lower in advanced AMD compared to early/intermediate AMD. Intermediate AMD was associated in our cohort with decreased serum FH levels together with increased serum mCRP/FH ratio. All these objective serum biomarkers may suggest an underlying systemic inflammatory process in early/intermediate AMD patients.